Silicon dioxide planarization: impacts on optical coatings for high energy lasers - Day, Travis E., author; Menoni, Carmen, advisor; Marconi, Mario, committee member; Williams, John, committee member (Colorado State University. Libraries, 2017)
The work of this thesis is devoted to examining the impact of silicon dioxide (silica or SiO2) planarization on the optical properties and laser damage resistance of thin-film coatings. SiO2 planarization is a process to smooth out fluence limiting nodular defects within multilayer coatings for high-energy laser applications. Mitigating these defects will improve the power handling abilities and improve the lifetime of laser coatings. Presented here is a combination of work with the aim of evaluating the optical and laser damage properties of SiO2 planarization within single layers, bilayers, and multilayers. As compared to control (non-planarized) samples, a 2-3x increase in the thin-film absorption, which decreases with post-process annealing, was discovered for SiO2 planarized samples. This suggests that planarization creates oxygen-related defects which can be annealed out and little impurity implantation. Investigations of laser damage resistance were carried out at λ = 1030nm and pulse durations of τ = 220ps and 9ps. The laser damage of single and bilayer coatings is known to be dependent on the substrate-coating interface and this is further evidenced within this thesis. This is because the effects of planarization are masked by the extrinsic laser damage processes within the single and bilayers. Slight change (<15%) in the laser induced damage threshold (LIDT) at 220ps and 9ps was observed for planarized single and bilayers. Depending on coating design, post-process annealing was shown to increase the LIDT by ~10% to ~75% at 220ps and ~10% to ~45% at 9ps. Although the fused silica substrate surface LIDT was shown to follow the √τ pulse scaling law for pulses above ~10ps, the single and bilayer coatings do not follow this pulse scaling. The divergence from the √τ pulse scaling on the coatings suggests a variation in the laser damage initiation mechanisms between 220ps and 9ps. Multilayer high-reflecting (HR) mirrors with varying planarization design were also damage tested. A 6-7 J/cm2 LIDT, with 220ps, was observed for HR coatings with SiO2 planarization layers within high electric-field areas within the coating. However, SiO2 planarization at the substrate-coating interface, where the electric-field is minimal, and control (non-planarized) was shown to have a LIDT of 63 ± 1.2 J/cm2 and 21.5 ± 0.5 J/cm2 for 220ps, respectively. At 9ps, the LIDT varied less than 90% difference between the various planarization designs. The substrate-coating planarization multilayer and control coating had an equal LIDT of 9.6 ± .3 J/cm2 at 9ps.
Keywords: multilayer coatings; silica; laser damage; silicon dioxide; planarization